Effect of mTOR inhibitors on sodium taurocholate cotransporting polypeptide (NTCP) function in vitro - Saran, Chitra; Ho, Henry; Honkakoski, Paavo; Brouwer, Kim L. R. (Frontiers in Pharmacology, 2023)
The sodium taurocholate co-transporting polypeptide (NTCP; gene name SLC10A1) is the primary hepatic basolateral uptake transporter for conjugated bile acids and the entry receptor for the hepatitis B and D virus (HBV/HDV). Regulation of human NTCP remains a knowledge gap due to significant species differences in substrate and inhibitor selectivity and plasma membrane expression. In the present study, various kinase inhibitors were screened for inhibition of NTCP function and taurocholate (TCA) uptake using NTCP-transfected HuH-7 cells. This study identified everolimus, an mTOR inhibitor and macrocyclic immunosuppressive drug, as an NTCP inhibitor with modest potency (IC50 = 6.7-8.0 µM). Further investigation in differentiated HuH-7 cells expressing NTCP and NTCP-overexpressing Flp-In T-REx-293 cells revealed that the mechanism of action of everolimus on NTCP is direct inhibition and is mTOR-independent. Structural analogs of everolimus inhibited NTCP-mediated TCA uptake, however, functional analogs did not affect NTCP-mediated TCA transport, providing further evidence for direct inhibition. This work contributes to the growing body of literature suggesting that NTCP-mediated bile acid uptake may be inhibited by macrocyclic peptides, which may be further exploited to develop novel medications against HBV/HDV.